Walai Kinabalu Cheese - Anthony, Laura; Majungga, Renly; Gandi, Rajip; Ahmad, Amirul; Johnny Orlando, Syasya Firzana Ashiqin (2015)
Our shop which known as Walai Kinabalu Cheese produced local cheese made from fresh milk supplied by Desa Cattle Dairy Farm from Kundasang Ranau, Sabah. Walai Kinabalu Cheese located at Ranau, Sabah. Our shop was located in strategic location which our target customer will easy to reach us and we also can save our time to get the fresh milk supply from ours supplier. Our target customer includes bakery shop, cake house, housewife and tourists. The different between our cheese products with the other cheese product was Walai Kinabalu Cheese use local fresh milk and keeps the cheese fresh when we sell it to customer. The cheese also produced in various shapes that will attract customer to buy it. In order to make their food more attractive, the cheese consumer can decorate their food with various colour of cheese. In addition, our business also provides delivery service to customers who want to buy in large quantity in area Sabah. We Walai Kinabalu Cheese saw the opportunity that this business has the potential of success in future because there is no other local cheese maker in Sabah. This is our big opportunity to be the first local cheese supplier in Sabah. As we know nowadays, the usage of cheese in baking cake is high then the demand of cheese will be increase in the future. Walai Kinabalu Cheese sees that by taking advantage of all these people's need, our business will prosper in this market.